2023
DOI: 10.1002/aenm.202302692
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Metastable Asymmetric Cu Single Atoms for Photoreduction of CO2 to Ethylene

Qingyu Wang,
Yida Zhang,
Minxi Lin
et al.

Abstract: Metastable structures are promising candidates for efficient catalysis owing to abundant active electronic states, strong electronic coupling with reactants, and energetic preference. Exerting the value of metastable structures while evading the difficulty in direct synthesis remains challenging. Herein, it is reported that light irradiation enables the generation and maintenance of the metastable state over copper single atoms for efficient carbon dioxide reduction. Under irradiation with light, photogenerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…As shown in Figure e, the C K edge sXAS spectra of 2% ReSe 2 /C 3 N 4 composites and pristine C 3 N 4 show two similar characteristic resonances, i.e., π* (CC) and π* (C–N–C) . Furthermore, the peak intensities of 2% ReSe 2 /C 3 N 4 composites decrease after the incorporation of ReSe 2 UTNs, implying the presence of vacancy defects in 2% ReSe 2 /C 3 N 4 composites because of lattice distortion caused by ReSe 2 incorporation . Electron paramagnetic resonance spectroscopy (Figure S4) shows that 2% ReSe 2 /C 3 N 4 composites possess more vacancy defects than does pristine C 3 N 4 .…”
Section: Resultsmentioning
confidence: 82%
“…As shown in Figure e, the C K edge sXAS spectra of 2% ReSe 2 /C 3 N 4 composites and pristine C 3 N 4 show two similar characteristic resonances, i.e., π* (CC) and π* (C–N–C) . Furthermore, the peak intensities of 2% ReSe 2 /C 3 N 4 composites decrease after the incorporation of ReSe 2 UTNs, implying the presence of vacancy defects in 2% ReSe 2 /C 3 N 4 composites because of lattice distortion caused by ReSe 2 incorporation . Electron paramagnetic resonance spectroscopy (Figure S4) shows that 2% ReSe 2 /C 3 N 4 composites possess more vacancy defects than does pristine C 3 N 4 .…”
Section: Resultsmentioning
confidence: 82%
“…To unveil the charge transfer mechanism in photocatalysis, in situ soft X-ray absorption spectroscopy (sXAS) and in situ electron paramagnetic resonance (EPR) have been performed over Co-OAc as a representative. The peaks at 778.4 and 793.7 eV correspond to the L 3 and L 2 edges, respectively (Figure a), which arise from the electron transition from p-orbitals to d-orbitals . Notably, the signals under light irradiation are apparently suppressed, suggesting that the Co sites accept electrons .…”
Section: Results and Discussionmentioning
confidence: 98%
“…50 Notably, the signals under light irradiation are apparently suppressed, suggesting that the Co sites accept electrons. 50 Furthermore, in situ EPR shows a Co 2+ signal under dark conditions (Figure S20). 51 Upon exposure to light, a reduced signal can be observed as the Co 2+ accepting electrons is converted into EPR-silent Co + .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the SACs with LFHPs for other catalytic reactions were exclusively based on Pt SAs directly anchored on halide perovskites via Pt coordination with the halide anions in the halide perovskites. With the aid of the surface coordination chemistry tuning, the exploration of other SAs to be anchored onto LFHPs through various coordination bonds could lead to new functionalities. In particular, it is envisaged that the incorporation of Cu SAs could be highly promising as Cu is regarded as one of the most attractive metal cocatalysts for CO 2 reduction owing to its optimal binding ability with CO 2 and reaction intermediates. , The superiority of Cu SAs on other photocatalysts for robust CO 2 reduction have also been validated. Furthermore, the immobilization of dual-atom or dual-single atom catalysts (DACs) on LFHPs is also worth exploring for selectivity tuning. Attributed to the mutual action of neighboring two atoms, it has been reported that DACs can outperform SACs through two metal active sites engineering, where DACs could efficiently stabilize the target intermediates leading to the desired products. …”
Section: Challenges and Future Prospectsmentioning
confidence: 99%